AVTOMATIK BOSHQARISH NAZARYASIDA ELEKTROMASHINALARNI CHASTOTA O‘ZGARTIRGICHINI PRINSIPIAL SXEMALARI ISHLASHINING TAHLILI. (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation This thesis analyzes the principle schemes of operation of frequency converters in the control of electric machines in the theory of automatic control. The theory of automatic control is a scientific field aimed at automating the control and management of systems, and through this theory, efficient and stable operation of systems is ensured. System optimization, error reduction and resource saving are the main goals of automatic control systems. Electric machines are widely used in areas where high efficiency and energy efficiency are required. Frequency converters (VFD - Variable Frequency Drive) are an important tool for controlling the rotation speed of electric machines. In this thesis, the basic principles of operation of VFDs, their role in the automatic control system and the scheme for increasing their efficiency are considered. Also, problems in the control of electric machines and ways to solve them are considered, especially the performance characteristics of frequency converters, their impact on the electromagnetic environment, and the possibilities of increasing system efficiency are analyzed. In this work, theoretical and practical approaches are combined, and recommendations are given regarding the parameters and controllers necessary for the optimization of the system.